Sintesis Nanopartikel Perak menggunakan Ekstrak Kulit Sirsak sebagai Bioreduktor - Riska Yudhistia Asworo; Hanandayu Widwiastuti; Elok Widayanti (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Soursop peel can be used as a bioreductor in the green synthesis process of silver nanoparticle formation. This is because the content of secondary metabolite compounds in soursop peel can reduce Ag3+ to Ag0 in nano size. Secondary metabolites in soursop peel are obtained by extraction using a solvent whose polarity value is close to the polarity value of soursop peel secondary metabolites. In this study, ethanol-aquadest and ethanol solvents were used. The extract obtained was then formulated with AgNO3 solution with a concentration variation of 0.5; 1; 1.5 and 2 mM to determine the optimum concentration on the formation of silver nanoparticles. The maximum concentration was obtained at a concentration of 2 mM AgNO3, seen from the highest absorbance obtained at the maximum wavelength observation of 400-450 nm with the concentration of AgNO3 used 2 mM. The silver nanoparticles formed were then analysed using a Particle Size Analyzer (PSA) to determine the size of the nanoparticles formed. Nanoparticles using ethanol-aquadest solvent had a size of 92.83 nm, while those using ethanol solvent had a size of 301.3 nm.